Socio-economic Conditions of Flood Affected People of Northern Districts in Bangladesh - Faruque, Omar (ABC Journal of Advanced Research, 2021)
In 2017, the death toll from floods sweeping in northern areas of Bangladesh has climbed above 150. In Dinajpur, Rangpur, Lalmonirhat, Kurigram and Thakurgaon more than 57.18 lakh people have been affected by flood and 6.11 lakh hectares of land damaged by floods in 32 districts Flood is an important natural disaster that deeply destroys the infrastructure and socio-economic conditions of the area. After the flood, the flood victims are feeling very unlucky. Their crops are totally destroyed. They are uncertain about their future. They do not know what would be happened in tomorrow. This study is conducted to find out the real situations of the flood victims of the said areas. The primary objective of this study is to provide a review of the socio-economic conditions of flood-affected people of northern districts in Bangladesh. To develop the paper, primary as well as secondary data is used. The quantitative, as well as qualitative analysis, is conducted for the study. Primary data is collected through a set of well-structured questionnaires. To collect the primary data, a personal survey method is used. Computerized modern technology is applied in the coding, tabulating, and processing of data. The victims are asked for their perceptions of life. It reveals that no victim is extremely pleased with their life before and after the flood, and 35% of victims were pleased before the flood, but after the flood, that rate is reduced to 8%. On the other hand, 5% of victims were extremely displeased, but after the flood that is increased to 17%. Floods have huge consequences on people, economics, and the environment. Flooding of regions used for socioeconomic activities produces a variety of negative effects. The government has various programs for food, housing, medical, and education but that is not enough. It is very little than the affected people. Providing adequate support for flood-affected people and preventing floodwaters can save the people of the river basin. It is also revealed that, by solving some problems locally, some nationally, and some internationally, it is possible to fill the lives of flood-affected people with laughter and joy.